An assessment of composite repair system in offshore platform for corroded circumferential welds in super duplex steel pipe (Fracture and Structural Integrity, 2018)
The main aim of this study is to assess the effectiveness of a composite repair system in severely corroded circumferential welds in super duplex stainless steel pipes as a preventive measure against the premature corrosion damage at the welds. Artificial defects were fabricated on the super duplex steel tube in order to reproduce the localized corrosion damage defects found in real welded joints. Three kinds of through thickness defects were considered: 25%, 50% and 96% of the perimeter of the pipe. The performance of the repaired pipe was assessed by hydrostatic tests as per ISO 24817 standard. The results showed that the composite repair system can sustain the designed failure pressure even for the pipe damaged with through-wall defect up to 96% of the perimeter of the pipe. Hence, the composite repair system can be used as a preliminary tool to protect the unexpected or premature failure at the welds and maintain an adequate level of mechanical strength for a given operating pressure. This composite repair system can assure that the pipe will not leak until a planned maintenance of the line. Nevertheless, further work is still desirable to improve the confidence in the long-term performance of bonded composite.
Keywords: Pipe repair; Super duplex steel; Corrosion; Composites; Hydrostatic tests; Offshore